Optimal Decision and Coordination of Fresh E-Commerce Supply Chain Considering Double Loss - Shizhen Bai; Yang Lv; Zejun Liu (Discrete Dynamics in Nature and Society)
Motivated by a large amount of quality loss and quantity loss of fresh products during transportation, this paper examines the effect of the double loss on decisions and profits by establishing models for a fresh e-commerce supply chain consisting of one online retailer and one third-party logistics provider. The online retailer sells fresh products and provides compensation for quantity loss. TPL’s fresh-keeping effort during transportation can effectively reduce the double loss. We find that: (i) under the centralized model, the basic quantity loss rate and freshness sensitivity can improve fresh-keeping effort. The online retailer prefers price-raising strategies as the basic quantity loss rate increases and freshness sensitivity decreases. But, if fresh-keeping cost is within a certain range and the basic quantity loss rate is high enough, the online retailer prefers price reduction strategies. If fresh-keeping cost is high, as freshness sensitivity increases, the retailer first reduces prices and then raises prices. (ii) Under the decentralized model, as the basic quantity loss rate and freshness sensitivity increase, product price will increase. (iii) Centralized decision-making mode is more profitable to the supply chain. Furthermore, we design a “two-way cost sharing-revenue sharing” contract to coordinate the supply chain and achieve Pareto improvement.